2022
DOI: 10.2174/1570180819666211230123145
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Inhibitors for Severe Acute Respiratory Syndrome-related Coronavirus 2 (SARS-CoV-2) Angiotensin-converting Enzyme 2 and the Main Protease from Anatolian Traditional Plants

Abstract: Background: The 2019 novel coronavirus disease (COVID-19) has caused a global health catastrophe by affecting the whole human population around the globe. Unfortunately, there is no specific medication or treatment for COVID-19 currently available. Objective: It’s extremely necessary to apply effective drug treatment in order to end the pandemic period and return daily life to normal. In terms of the urgency of treatment, rather than focusing on the discovery of novel compounds, it is critical to explore the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…These studies involved predicting various parameters, including octanol/water partition coefficient, aqueous solubility, apparent Caco‐2 cell permeability, brain/blood partition coefficient, apparent MDCK cell permeability, human oral absorption prediction on a scale of 0–100 %, as well as assessing the number of violations of Lipinski's rule of five and Jorgensen's rule of three parameters. These predictions were made to evaluate the compounds′ suitability for drug development [49] . The ADME prediction outcomes for the target compounds have been compiled in Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies involved predicting various parameters, including octanol/water partition coefficient, aqueous solubility, apparent Caco‐2 cell permeability, brain/blood partition coefficient, apparent MDCK cell permeability, human oral absorption prediction on a scale of 0–100 %, as well as assessing the number of violations of Lipinski's rule of five and Jorgensen's rule of three parameters. These predictions were made to evaluate the compounds′ suitability for drug development [49] . The ADME prediction outcomes for the target compounds have been compiled in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…These predictions were made to evaluate the compounds' suitability for drug development. [49] The ADME prediction outcomes for the target compounds have been compiled in Table 3. Typically, there are two critical descriptors that determine whether a molecule can be classified as a potential drug.…”
Section: In Silico Adme Studiesmentioning
confidence: 99%
“…To predict the physicochemical descriptors, pharmacokinetic properties, and drug‐likeness of all the compounds ADME (absorption, distribution, metabolism, and excretion) studies were performed. In in silico ADME studies, predicted octanol/water partition coefficient, predicted aqueous solubility, predicted apparent Caco‐2 cell permeability in nm/sec., predicted brain/blood partition coefficient, predicted apparent MDCK cell permeability in nm/sec., predicted human oral absorption on 0–100 % scale, number of violations of Lipinski's rule of five, and number of violations of Jorgensen's rule of three parameters were determined and evaluated [24] . ADME prediction results of the target compounds were summarized in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…In in silico ADME studies, predicted octanol/ water partition coefficient, predicted aqueous solubility, predicted apparent Caco-2 cell permeability in nm/sec., predicted brain/blood partition coefficient, predicted apparent MDCK cell permeability in nm/sec., predicted human oral absorption on 0-100 % scale, number of violations of Lipinski's rule of five, and number of violations of Jorgensen's rule of three parameters were determined and evaluated. [24] ADME prediction results of the target compounds were summarized in Table 3. There are generally two important descriptors for molecules to be considered a drug.…”
Section: In Silico Adme Studiesmentioning
confidence: 99%
“…were assessed in terms of their potential antiviral activity against SARS-CoV-2 by molecular docking. It was found that among others, chlorogenic acid can be regarded as an anti-SARS-CoV-2 agent with potent protease inhibitory activity ( Kılınç et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%